THE RELATIONSHIP OF KNOWLEDGE WITH MOTHERS' ATTITUDES ABOUT INFANT FEEDING AND STUNTING CHILDREN IN NGALANG GUNUNGKIDUL - Sunarsih, Tri; Hikmah, Friska Nurul; Yulaikhah, Lily Lily (Siklus : Journal Research Midwifery Politeknik Tegal, 2024)
Stunting refers to a condition characterized by the failure of a toddler to achieve optimal growth and development, primarily attributable to sustained inadequate dietary intake leading to chronic energy deficiency. Consequently, children affected by stunting exhibit a diminished stature compared to their peers of the same age cohort. The primary objective of this study was to ascertain the potential correlation between maternal knowledge levels and attitudes concerning infant and child feeding practices amidst instances of stunted growth, specifically focusing on the context of Ngalang Village within the Gunungkidul region of Yogyakarta, Indonesia. This type of quantitative research uses a cross-sectional approach. The study encompassed the entire demographic of mothers with children aged 0 to 60 months exhibiting stunted growth within Ngalang Village, Gunungkidul, comprising 85 respondents. The sample was selected using a purposive sampling technique, using the Slovin formula, and a sample of 46 respondents was obtained.  Statistical analysis was conducted using the chi-square test and obtained a p-value of 0.504 (< 0.05). This study concludes that there is no significant influence between knowledge and maternal attitudes about stunting infant and child feeding (PMBA) in Ngalang Village, Gunungkidul, Yogyakarta. The next researcher should look at the factors of the living environment so that it can be known whether the environment in which they live affects attitudes.